KARAKTERISTIK KIMIA DAN SENSORI PENYEDAP RASA LIMBAH UDANG KOMBINASI JAMUR TIRAM METODE FOAM-MAT DRYING - Ilma, Azka Af'idatul; ., Siti Aminah (Universitas Muhammadiyah Semarang, 2024)
Shrimp waste flour and oyster mushroom were developed into flavoring using the foam-mat drying method. This study aims to determine the effect of the formulation on water content, glutamate content, sensory characteristics and determine the best treatment for flavoring. The study used an experimental method with a completely randomized design (CRD), with 7 formulation of shrimp waste and oyster mushroom with a ratio of P1 (0:100), P2 (100:0), P3 (30:70), P4 (40:60), P5 (50:50), P6 (60:40), P7 (70:30). Parameters analyzed included chemical (water content and glutamate content), sensory (color, texture, aroma and taste). The results of this study indicate that the combination of the ratio of shrimp waste and oyster mushrooms has an effect on decreasing water content, increasing glutamate levels and sensory (color, aroma, texture, and taste). The higher the level of shrimp waste, the better the product will be. The addition of shrimp waste can further increase the nutritional value of the flavoring. The best formulation for flavoring is P7 with a ratio of shrimp waste and oyster mushroom (70:30).